Raising ’kyoto Forests’ in the Different Bio-geographic Zones of India - a Profitability Analysis - Kant, Promode (Indian Forester, 2005)
The cost of carbon sequestration under the Clean Development Mechanism (CDM) of the Kyoto Protocol is far higher than the normal afforestation costs as it includes the opportunity cost of the land and the costs of project formulation, regeneration, maintenance, monitoring, measuremcnt, verification, baseline construction, leakage accounting, accessing markets and the costs incurred in ensuring additionality, biodiversity conservation and the credibility of the certification system. For purposes of reforestation of degraded forests the ecosystem productivity of the bio.geographic zones in which these forests lie also influences the costs to a very high degree. In India the land rentals alone exceed the current tentative price range of carbon. The withdrawal of the USA from the Kyoto Protocol, the very real possibility of trade in ’hot air’ and the limitations on the use of carbon credits earned through carbon sequestration under the CDM would make a demand induced price rise for carbonoeredits unlikely. Also, demand for higher volumes of carbon sequestered in forests may also drive the costs up, as greater requirement for land would enbance its rental, notwithstanding the advantages of the economy of scale. The high transaction costs, arising out of the stringent Kyoto conditionalities and monitoring quality expected of the CDM projects, present another formidable barrier to the profitability of such sequestration projects.